Rural Development with Agroecological Emphasis for Highly Marginalized Areas in Mexico: The Bet for Paradigm Change (Global Journal of Human-Social Science, 2024)
For four years the Production for Well-being Program has been developed which consists of three axes of operation direct support to producers marketing and technical support in 11 production chains in 27 states of the Mexican Republic with more or less than 600 municipalities of high marginalization the accompaniment is implemented by the National Institute of Forestry Agriculture and Livestock Research INIFAP the central objective of the program is food self-sufficiency through the agroecological transition the results indicate that at least in the In the first three years agroecological work practices plant nutrition and soil bioremediation have been adopted through the production of local bio-inputs by the producers in addition to the rescue and conservation of native resources mainly corn as well as a holistic vision of management of the Rural Production Unit UPF The program places special emphasis not only on the promotion of agroecological practices but also on inclusion and gender equity as evidenced by the 34 participation of women
Keywords: food self-sufficiency; marginalized areas; agroecology